2020
DOI: 10.1136/rmdopen-2019-001144
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the sensitivity to change of the OMERACT ultrasound structural gout lesions during urate-lowering therapy

Abstract: ObjectivesTo evaluate the sensitivity to change of ultrasound structural gout lesions, as defined by the Outcome Measures in Rheumatology (OMERACT) ultrasound group, in patients with gout during urate-lowering therapy (ULT).MethodsUltrasound (28 joints, 26 tendons) was performed in patients with microscopically verified gout initiating or increasing ULT and repeated after 3 and 6 months. Joints and tendons were evaluated by ultrasound for presence of the OMERACT structural gout lesions—double contour sign (DC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…Previous researchers have taken benzbromarone in consideration during ULT research. 2 Also, the proportions and a subgroup analysis of patients using different medicines (allopurinol and febuxostat) are recommended for verifying effectiveness. Last but not the least, according to European League Against Rheumatism (EULAR), a lower target (under 5 mg/dL or 300 μmol/L) might be given if patients have severe gout with tophi, chronic arthropathy or very frequent attacks.…”
mentioning
confidence: 99%
“…Previous researchers have taken benzbromarone in consideration during ULT research. 2 Also, the proportions and a subgroup analysis of patients using different medicines (allopurinol and febuxostat) are recommended for verifying effectiveness. Last but not the least, according to European League Against Rheumatism (EULAR), a lower target (under 5 mg/dL or 300 μmol/L) might be given if patients have severe gout with tophi, chronic arthropathy or very frequent attacks.…”
mentioning
confidence: 99%
“…In fact, it is one of the most common US finding indicating MSU deposits in patients with both early and established gout [11,33]. Moreover, it was the most sensitive to change US feature in patients undergoing ULT [12][13][14][15]34]. Therefore, the presence of DC sign is a strong imaging biomarker that should induce the clinicians to maintain or even to increase the ULT.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although the US MSU burden was significantly lower in patients who fulfilled the remission criteria, MSU deposits were still detectable by US in a relevant number of these patients ranging from 19.0% with DC sign to 47.6% with aggregates. The US identification of aggregates in patients in clinical remission (47.6%) may be explained by the new formation of aggregates from the dissolution of larger tophi [12,13] or by the misinterpretation of non-crystalline hyperechoic spots [26], as the specificity of OMERACT-defined aggregates has been recently questioned [35]. The persistence of tophi even in patients in clinical remission (38.1%) may be related to a "dense" collection of MSU crystals requiring a more aggressive or a more prolonged ULT or to the histological composition of the tophus itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that ultrasound-detected crystal depositions gradually decrease and reduce tophi size during efficient ULT (12)(13)(14). However, to our knowledge, there are only two recent studies that have reported a scoring system to quantify changes in aggregates, erosion, and the DCS (15,16). These studies demonstrated that USdetected urate crystal depositions were reduced during effective ULT, thus encouraging clinicians and gout patients to persist in the treat-to-target approach of ULT (15,16).…”
Section: Introductionmentioning
confidence: 99%